Aplikasi Deteksi Warna Berbasis Mikrokontroler : Mewujudkan Solusi Cerdas dalam Identifikasi Visual - Rahmadani Fitri Panjaitan (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
This study aims to develop a color detection application based on microcontrollers as an intelligent solution for visual identification. The application is designed to accurately detect and identify color spectrums using a color sensor integrated with a microcontroller. A project management approach in informatics engineering was applied to ensure the effective design and implementation of the system. A qualitative descriptive method was employed in this research, including data collection through device testing and interviews with potential users. The results demonstrate that the application can recognize colors with high accuracy, making it applicable across various fields such as industry, education, and assistive technology. Supporting factors for the application's success include hardware and software compatibility, while the main challenges involve the impact of light intensity on sensor performance. Further development is recommended to enhance the application’s performance in more diverse operational environments.